2015
DOI: 10.1371/journal.pone.0142080
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum Pepsinogens as a Biomarker for Gastric Cancer and Atrophic Gastritis Screening: A Systematic Review and Meta-Analysis

Abstract: BackgroundHuman pepsinogens are considered promising serological biomarkers for the screening of atrophic gastritis (AG) and gastric cancer (GC). However, there has been controversy in the literature with respect to the validity of serum pepsinogen (SPG) for the detection of GC and AG. Consequently, we conducted a systematic review and meta-analysis to assess the diagnostic accuracy of SPG in GC and AG detection.MethodsWe searched PubMed, Embase, and the Chinese National Knowledge Infrastructure (CNKI) for cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 59 publications
3
127
1
11
Order By: Relevance
“…A 2015 meta-analysis by Huang et al . [18] calculated a pooled 69% (95% CI, 52-83%) sensitivity, 84% (95% CI, 68-93%) specificity and ROC AUC of 0.83 (95% CI, 0.80-0.86) for PgI/PgII. Our results are generally comparable.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 meta-analysis by Huang et al . [18] calculated a pooled 69% (95% CI, 52-83%) sensitivity, 84% (95% CI, 68-93%) specificity and ROC AUC of 0.83 (95% CI, 0.80-0.86) for PgI/PgII. Our results are generally comparable.…”
Section: Discussionmentioning
confidence: 99%
“…This is characterised by corpus predominant gastritis, gastric atrophy/intestinal metaplasia, hypochlorhydria, and evidence of current or past H. pylori infection. Screening on a population-wide basis by invasive approaches is not feasible but the gastric cancer phenotype can be detected by a combination of non-invasive markers including H. pylori serology and pepsinogen levels (Pgl or Pgl/II ratio) 333 334. Genomic approaches are also promising but require validation in prospective studies 335.…”
Section: Working Group 4: Prevention/public Healthmentioning
confidence: 99%
“…However, by serological examination, significant differences of PG I/II ratio between AG+GG genotypes and AA homozygotes were not observed in older patients (age >60 years old), although it was significantly different in younger age groups (age ≤60 years old). Sydney system scores express the severity of gastritis at a biopsy point, whereas PG I/II ratio express the spread of mucosal atrophy (16,26). It has been reported that the significant association between serum and histological atrophy is more strongly observed in the corpus compared with in the antrum (27).…”
Section: Discussionmentioning
confidence: 99%